Cranial anatomy and morphometry of Coryphospingus pileatus (Wied, 1821) (Passeriformes: Thraupidae) - Lima, Mônica da Costa; Mariano, Erich de Freitas; de Brito, Wenner Justino Bezerra; de Souza, Joyce Galvão; Carreiro, Artur da Nóbrega (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2019)
Granivorous animals are among the most abundant in dry regions where, this feeding strategy seems to be successful because of the availability, diversity and stability of seed resources. This feeding strategy is successful for Coryphospingus pileatus. However, the cranial anatomy of this species is little known. The aim of this paper was to describe the cranial osteology of C. pileatus, a granivorous-insectivorous bird from the neotropical region, to measure its craniometric data and to understand a little about the relationship among the skull, feeding behavior, and ecology of the specie and to identify which characteristics can be used in future studies. Four specimens were used, which were dissected, described, measured, weighed, and drawn. The structures observed in the cranium of C. pileatus present particularities of the specie and characteristics found in the other passerines. The main anatomical features are in the beak, such as the conical beak, robust and with sharp edges associated with the habit of peeling seeds, and orbits, in which there is a possible relation with the ecology and behavior of the species. Studies of anatomy and morphology are important in deepening our knowledge, providing more background information for further comprehensive studies.
Keywords: Skull; Craniometric measurements; Birds